Evaluation of the electro-dress Mollii® to affect spasticity and motor function in children with cerebral palsy: Seven experimental single-case studies with an ABAB design. Issue 1 (31st December 2022) - Arkkukangas, Marina; Hedberg Graff, Jenny; Denison, Eva
Abstract: There are limited non-invasive treatment options in the home environment for children with cerebral palsy (CP); thus, evaluating such treatment options is needed. We aimed to evaluate the effect of an innovative full-body suit approach for non-invasive surface electrical stimulation ES, the electro-dress Mollii®. The full-body suit was primarily designed to reduce spasticity and improve motor function through the mechanism of reciprocal inhibition among children with CP. This study involved seven experimental single-case studies with an ABAB design. Seven studies were performed among children aged 4–17 years. The primary outcome (spasticity) was analyzed using graphed data with a visual inspection, and median values were analyzed for secondary outcomes (mobility, sitting, upper limb activity, sleep, pain, and adherence to treatment). The study protocol was recorded at clinicaltrials.gov (NCT04078321). Seven studies were analyzed, and the treatment with the electro-dress had little or no impact on the outcomes: spasticity, mobility, sitting, upper limb activity, sleep, and pain, in any of these seven studies. In conclusion, multiple ES treatment with the innovative electro-dress Mollii® revealed little or no observable changes on primary outcome (spasticity) in any of the seven studies. Further the possible impact on motor function is recommended to be further evaluated in future studies